Szkoła na wolnym powietrzu – projekty mebli E. Beaudoina i M. Lodsa dla szkoły w Suresnes (1932–1935) w świetle przemian w pedagogice i projektowaniu wnętrz szkolnych we Francji lat 20. i 30. XX wieku - Jędruch, Dorota (Artium Quaestiones, 2021)
The essay is devoted to the relationship between the design of school furniture and other interior design elements in the open-air school (école de plain air) in Suresnes (designed by E. Beaudoin and M. Lods, 1932–1935) and the pedagogical and social assumptions accompanying its construction. The functioning of the school and the role that furniture plays in this program are discussed, as well as how the furniture design responded to the interesting pedagogical program of the international outdoor school movement. The second part of the text discusses the main trends in the design of school furniture in France in the interwar period. Architects’ theoretical views on the problem of so-called “new education” in the design of school buildings and their equipment (mainly texts and projects by Maurice Barret, published in “Architecture d’aujourd’hui”). Trends in furniture design are presented against the background of the pedagogical concepts of that era: Maria Montessori’s pedagogy and progressive trends in teaching, under the influence of which class spaces began to be designed as rooms with flexible functions, thanks to features such as light, multi-functional school furniture using modern shapes and materials.